Comparison of Some Physical Properties of Foam Concentrates - Pyronil and Alfa A - Zachar, Martin (Communications - Scientific letters of the University of Zilina, 2005)
The choice of a suitable foam concentrate is the first precondition of achieving a foam (as an extinguishing agent) with optimal properties to extinguish A and B class fires. On the basis of the given facts, this article compares some physical properties of foam concentrates and their effect on the environment (environmental friendliness).